Seat optimization for single handed paralympic sailing boat - van Stein Callenfels, K. L.; van der Ent, M.; Berger, M. A. M. (Procedia Engineering, 2016)
PURPOSE: The aim of this study was to optimize the seat for the skipper of a 2.4mR, a Paralympic sailing boat (single-hander). Primarily, the seat was designed for a man with diastrophic dysplasia, a disorder of cartilage and bone development. This 39 year old man has a short stature with very short arms and legs and joint deformities which restrict movement. The skipper's main tasks are handling the rudder and the mainsheet using small ropes with his hands and pedals with his feet. He is sitting on a seat attached to the floor of the boat, while his body is positioned facing the bow of the boat. The combination of movements of the boat and tasks during sailing resulted in a constantly changing instability of the body. This might declare some of the injuries (pain in hips, knees and shoulders) that were called. The design goal for the seat was to find an optimum in body stability and range of motion during sailing. METHODS: An analysis of the possible movements in the frontal and sagittal plane of the skipper in the boat was made using a mock-up. A movement analysis of sailing was made in three boat conditions: 1. Boat heeling 32° (sailing close hauled), bodyweight as much windward as possible in the hull; 2. No boat heeling (reaching), bodyweight in front of the seat; 3. No boat heeling (reaching), bodyweight at the back of the seat. A biomechanical analysis was made in order to estimate the forces on the body in the three boat conditions where the boat heeling and the position of the bodyweight of the sailor are varied. An iterative design process was followed which resulted in different prototypes and finally in a new seat. RESULTS: The main requirement on the seat is that it should prevent sliding on the seat in the frontal plane, especially in condition 1. Then, a friction coefficient of 0,63 is needed. Three prototypes have been build and tested. The final design consists of an aluminium seat with three sloping surfaces and a backrest that stabilizes the body. The seat can slide 19 cm forwards and backwards. CONCLUSION: The third prototype has been tested in the lab and on the water. Freedom of movement and stability were enhanced. The prototype is further developed and applied for different Paralympic sailors and sailboats.